ANALISIS PENERAPAN METODE TASMI’ DAN JUZ’I DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN - Gunawan, Hanif Sunni; Shohib, Muhammad Wildan (PAI RAFAH, 2023)
This research aims to find out: 1) how the tasmi' and juz'i methods are applied in improving the quality of memorizing the Al-Qur'an at the Muhammadiyah Boarding School Tahfizhul Qu'an Wonopringgo, 2) the application of the tasmi' and juz'i methods effective in improving the quality memorizing the Qur'an at the Muhammadiyah Boarding School Tahfizhul Qu'an Wonopringgo, 3) what factors support and hinder the implementation of the tasmi' and juz'i methods at the Muhammadiyah Boarding School Tahfizhul Qu'an Wonopringgo. This research includes field research with a qualitative approach. The data collection techniques were obtained from observation, interviews, and documentation. Meanwhile, data analysis for this research includes data collection, data reduction, data presentation, and verification of conclusions. The results of this research show 1) the application of the tasmi' and juz'i methods at the Muhammadiyah Boarding School Tahfizhul Qu'an Wonopringgo is structured and well, 2) the tasmi' and juz'i methods are effective methods to apply because they can improve the quality of memorization, 3) the achievement of the tasmi' and juz'i methods are influenced by inhibiting and supporting factors. Supporting factors include motivation from the people around you, a strong will to achieve targets, a conducive environment, and a structured schedule. Meanwhile, inhibiting factors include laziness, lack of time management, and lack of self-confidence.